Would a simple attention-reminder in discrete choice experiments affect heuristics, preferences, and willingness to pay for livestock market facilities? - Kassie, Girma T.; Zeleke, Fresenbet; Yitayih, Mulugeta; Scarpa, Riccardo (2022)
This study addresses the question whether an ‘attention reminder’ in discrete choice experiments (DCE) affects preferences, willingness to pay (WTP), and attribute non-attendance (ANA). We report on an experiment which elicited preferences for livestock market facilities from 960 randomly selected farm households in Ethiopia. Basic diagnostic comparisons of the estimations showed that taste parameters are significantly different and the WTP values of two (out of eight) facilities are different betweenbeforeandafterthe reminder. Latent class model based ANA analysis revealed that the reminder has increased fully compensatory choice behavior [full attention] among sample respondents. The mixed logit models estimated in WTP space also showed that the WTP values are slightly smaller for most of the facilities after the reminder. In terms of relative importance, veterinary clinic, fenced shed, and watering trough facilities are the three livestock market facilities valued most by the farm households bothbeforeandafterthe reminder. Our results imply that researchers studying behaviors of rural communities in developing countries using DCEs might be able to address issues related to heuristics if they reminded respondents of the need to pay attention to all elements in the experiment unless understanding the choice decision making process itself is the point of interest. Empirically, livestock market development initiatives need to take into account farmers’ clear and consistent prioritization of the market facilities.